2015
DOI: 10.3389/fpubh.2015.00255
|View full text |Cite
|
Sign up to set email alerts
|

Building Partnership to Improve Migrants’ Access to Healthcare in Mumbai

Abstract: ObjectivesAn intervention to improve migrants’ access to healthcare was piloted in Mumbai with purpose of informing health policy and planning. This paper aims to describe the process of building partnership for improving migrants’ access to healthcare of the pilot intervention, including the role played by different stakeholders and the contextual factors affecting the intervention.MethodsThe process evaluation was based on Baranowski and Stables’ framework. Observations in community and conversations with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Publications in this category are studies focusing on health promotion and access to care, mainly implemented in the USA (19/36), Europe (12/36), and Canada (2/36), and in Australia (2/36) and Asia (1/36), mostly in between 2007–2018 [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. The populations addressed included racial and ethnic minorities; migrants (further specified as elderly, farm workers, or irregular); refugees (Syrian, apartment-dwelling, youth, older adult, and more); immigrants (elderly or recent); and minority children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Publications in this category are studies focusing on health promotion and access to care, mainly implemented in the USA (19/36), Europe (12/36), and Canada (2/36), and in Australia (2/36) and Asia (1/36), mostly in between 2007–2018 [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. The populations addressed included racial and ethnic minorities; migrants (further specified as elderly, farm workers, or irregular); refugees (Syrian, apartment-dwelling, youth, older adult, and more); immigrants (elderly or recent); and minority children.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalent aspects of interventions were: supervision and responsibility of stakeholders to provide equity, cultural, and linguistic competence in healthcare access and delivery [86,87]; creating a sense of community and commitment; obligation of stakeholders [68,[86][87][88]; community-based leadership that is transferring the operational supervision of the intervention to the local level to facilitate sustainability [79,89]; social networking viewed as a necessary skill along with good communication to improve the efficiency of the intervention [89,90]; and evidence-based guidelines [91,92].…”
Section: Health Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers vulnerabilities are further compounded by the lack basic social, legal and health protection (4,6). Studies have also found that migrants are rarely able to access urban health services despite increased proximity to these services in the city (7,8). They are also excluded from government health programs in the destination region merely on account of being migrants (9).…”
Section: Introductionmentioning
confidence: 99%
“…Champions are motivated by their eagerness to see the platform operate successfully and to see the platform objectives realised (24,70,71,26,50,52,55,57,58,61,62)…”
mentioning
confidence: 99%